The Social Deviance Notion - DIACONESCU, Amelia (Journal of Advanced Research in Law and Economics, 2017)
The society affords to judge and assess the behavior of its members, according to the degree of conformity of the respective behavior to the accepted and unanimously recognized norms and values. By utilizing the social control and adaptation as ‘persuasive’ tools for the existing community, the society affords to transfer its members the normative and cultural model promoted by it. Subsequent to this ‘lesson’ where people learn the social roles which must be fulfilled, the long awaited reward is received – social integration. Each individual has the possibility to absorb knowledge, habits and rules and then apply them as an active member of the society. One of the main functions of the society is generating, maintaining and passing from generation to generation the values which define the specific of the society, its structural matrix. This function can be found at the level of the groups and social organizations. Such function is fulfilled through a fundamental social process, namely socialization.